Does paternal sterility impact on progeny germination and survivorship, case study in strawberries - Houshang NOSRATI (Acta Agriculturae Slovenica)
Studies on the parental role on progeny performance have mostly focused on the maternal parent, while less attention was given to the paternal parent. This study investigated the impact of paternal pollen sterility (ranging from 3.1 – to 77.2%) on F1 seed germination and progeny survivorship in Fragaria (strawberry, Rosaceae) using controlled crosses. In crosses within F. vesca ssp. vesca the paternal pollen sterility was not correlated with F1 seed germination (N = 14, p > 0.074) and progeny survivorship (N = 14, p > 0. 0.710). Paternal sterility in crosses between F. vesca ssp. vesca and F. vesca ssp. monophylla did not affect on F1 seed germination (N = 7, p > 0.295) and progeny survivorship (N = 6, p > 0.812). Similarly, no correlation was found between father pollen sterility and F1 seed germination (N = 6, p > 0.924) and progeny survivorship (N = 6, p > 0.215) in crosses between F. vesca ssp. americana and F. vesca ssp. vesca. Furthermore, crossing different maternal plants by pollen of the same paternal plant in all three cross types produced progeny with variable levels of F1 seed germination and survivorship. These results indicate the crucial role of maternal plant on progeny performance and support the general idea of the importance of maternal rather than paternal parent on progeny performance.